Managing economic volatility in Latin America - Gelos, Gaston; Werner, Alejandro M. (International Monetary Fund, 2014)
How has Latin America coped with external shocks and economic vulnerabilities in the aftermath of the global financial crisis? Managing Economic Volatility in Latin America looks at how the region has fared in recent years in an environment of uncertainty. It presents a collection of novel contributions on capital flows, terms of trade, and macroeconomic policy in Latin America. The rigorous expert analysis offers an up-to-date guide to many of the key economic policy questions in the region. Chapters focus on important analytical issues, including assessing reserves adequacy and current account levels. The roles of macroeconomic policies and exchange rates regimes in coping with large capital inflows are examined, as well as the effectiveness of both monetary policy and fiscal policy in dealing with economic challenges in the region--Back cover.